2018
DOI: 10.1080/00207454.2018.1441150
|View full text |Cite
|
Sign up to set email alerts
|

Serum uric acid levels and outcome during admission in acute ischaemic stroke, depending on renal function

Abstract: Our results support the hypothesis that hyperuricaemia plays a protective role in the prognosis of stroke, independently from renal function, and that even in patients with chronic kidney disease, it remains as a protective agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…We deemed that the SUA/Cr ratio would be more sensitive in predicting POD in older patients following urinary calculi surgery, which might be a result of eliminating the effect of renal function on UA. 40 Similar to our research, prior studies demonstrated the SUA/Cr level in patients with Parkinson’s disease (PD) was lower and was negatively associated with the stages of PD. 41 , 42 Nevertheless, other studies indicated the high SUA/Cr ratio could result in poorer functions outcomes and the increased risk of stroke recurrence after ischemic stroke, which might be explained by the controversial role of UA and its physiological metabolism.…”
Section: Discussionsupporting
confidence: 89%
“…We deemed that the SUA/Cr ratio would be more sensitive in predicting POD in older patients following urinary calculi surgery, which might be a result of eliminating the effect of renal function on UA. 40 Similar to our research, prior studies demonstrated the SUA/Cr level in patients with Parkinson’s disease (PD) was lower and was negatively associated with the stages of PD. 41 , 42 Nevertheless, other studies indicated the high SUA/Cr ratio could result in poorer functions outcomes and the increased risk of stroke recurrence after ischemic stroke, which might be explained by the controversial role of UA and its physiological metabolism.…”
Section: Discussionsupporting
confidence: 89%
“…Chiquete et al [ 16 ] posited that the correlation between low concentration of UA and severity of acute cerebral infarction could be used as a marker of the degree of cerebral infarction. According to Arevalo-Lorido et al [ 17 ], NIHSS scores decrease with increasing UA, even in patients with cerebral infarction and abnormal renal function. In performing a randomized, double-blind, placebo-controlled phase 2b/3 trial in which UA was added during thrombolytic therapy administered to patients with acute cerebral infarction, Chamorro et al [ 18 ] found that UA had a protective effect on the patient's nerve function.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, rats receiving intraperitoneal UA infusions presented with antihypertensive and nephroprotective effects, probably due to the antioxidant effects of UA 9–11 . A protective role for UA during acute ischaemic stroke has also been reported 12–15 …”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] A protective role for UA during acute ischaemic stroke has also been reported. [12][13][14][15] In the absence of previous renal impairment, harmful hyperuricaemia-associated morphological changes have been reported in rat kidneys. 5,[16][17][18] A diet with 2% of the uricase inhibitor Oxo was found to increase collagen deposition, macrophage infiltration, juxtaglomerular renin staining and media-lumen ratio of afferent arterioles and induce glomerular hypertrophy in rat kidneys.…”
Section: Introductionmentioning
confidence: 99%